A WOMAN UNITED WITH THE SACRIFICE OF CHRIST – BLESSED KLEMENSA STASZEWSKA OSU (1890–1943) - Anna Emmanuela Klich (Forum Teologiczne)
The aim of this article is to examine the charism of Blessed Klemensa Staszewska, with which she was endowed by God, and its relevance to all believers. The sources of this study are her “spiritual notes”, written at the instruction of her spiritual director, and her letters. The first stage of the study examines how Blessed Klemensa, accepting her Ursuline vocation, experienced the desire for a spousal bond with Jesus and to give to Him alone all that she is and all that she possesses. In the second part of the article, a study is carried out on the spiritual desire expressed by Blessed Klemensa in her plan of life, written on the day of her perpetual vows to unite herself to the Sacrifice of Christ and to His intentions and the inner  disposition with which He offered Himself on the Cross. Here it was important to examine how Blessed Klemensa experienced all the tribulations and difficulties of life in union with Jesus. This dimension of her spiritual life can be regarded as prophetic for both consecrated and lay persons, because it concerns the universal priesthood resulting from baptismal consecration, which seems to be underestimated in Christian spirituality today. In the fourth and final part of the article, it is shown how Blessed Klemensa combined a deep spiritual life with her ministry of caring for children and the formation of young people. She maintained this life amidst her duties and responsibility for the Ursuline community throughout the hardships of World War II and when, after helping with heroic courage those sought by the Gestapo, she endured the cruelty of the concentration camp.